High Occurrence Among Calves and Close Phylogenetic Relationships With Human Viruses Warrants Close Surveillance of Rotaviruses in Kuwaiti Dairy Farms - Alotaibi, Mohammad A.; Al-Amad, S.; Chenari Bouket, Ali; Al-Aqeel, H.; Haider, E.; Hijji, A. Bin; Belbahri, Lassaad; Alenezi, Faizah N. (Frontiers in Veterinary Science, 2022)
Rotavirus, one of the main pathogens causing morbidity and mortality in neonatal dairy calves worldwide, is responsible for 30-44% of cattle deaths. It is considered to be the most common etiologic agent of diarrhoea in neonatal dairy calves and children, the dominant type being group A. Two hundred seventy animals from 27 farms from 2 regions of Kuwait were tested for the presence of Rotavirus serogroup A (RVA) using latex agglutination test (LAT) and reverse transcription – polymerase chain (RT-PCR) testing. RVA non-structural proteins NSP1-2, NSP4-5 and capsid protein genes VP1-7 were characterized by next generation sequencing. LAT was positive in 15.56% of the animals, and RT-PCR in 28.89%. Using RT-PCR as a reference method, LAT was 100% specific but only 83.33% sensitive. ANOVA analysis showed correlation only with the location of the farms but no significant correlation with the age and sex of the animals. Although there was a tendency of clustering of RVA positive animals, it did not reach statistical significance ((p=0.035 for LAT). The phylogenetic analysis showed that Kuwaiti isolates of group A rotavirus clustered with human rotaviruses. Taken together, it seems that rotavirus was present in most of the dairy farms in Kuwait. The high occurrence of the virus in calves in Kuwaiti dairy farms and the close phylogenetic affinity with human isolates warrants urgent action to minimize and control its spread between calves in farms.